DEVELOPMENT OF ENGLISH FOR SPECIFIC PURPOSES MODULES IN ISLAMIC EDUCATION LEARNING AT HIGHER EDUCATION INSTITUTIONS - Sulaiman, Muhammad; Suci Madiarti Isman; Ardik Ardianto; Lianasari, Lianasari; Firmansyah, Firmansyah (Conciencia, 2024)
This study aims to develop an English for Specific Purposes (ESP) module tailored to the needs of Islamic Education (PAI) programs in higher education institutions. The research employed a qualitative approach with a descriptive-exploratory method, involving three stages: (1) document observation, including the analysis of Syllabus (RPS) and existing teaching materials, (2) needs analysis through interviews and focus group discussions (FGDs) with faculty members and students, and (3) the design and development of ESP modules integrating Islamic content. The study was conducted at two Islamic universities in Indonesia, University A and University B, with participants comprising program heads, lecturers, and students from Islamic Education programs. The findings highlight several key points: University A lacks a structured ESP module, relying solely on RPS and inconsistent content across study programs. In contrast, University B demonstrates a more organized approach, with a dedicated ESP textbook titled English for Islamic Studies that incorporates Islamic themes, such as tafsir, fiqh, and aqidah. Additionally, University B effectively integrates digital tools and employs student feedback mechanisms to enhance engagement and flexibility in learning. Reading skills emerged as the most critical competency, supported by thematic Islamic content to improve linguistic and religious competencies. The study concludes that a well-structured ESP module aligned with institutional goals and students’ academic and spiritual aspirations can significantly enhance the teaching and learning process. These findings contribute to the broader discourse on ESP as a transformative tool for education in Islamic contexts.